A Real-Business-Cycle model with pollution and environmental taxation: the case of Bulgaria - Aleksandar Vasilev (Journal of Environmental Economics and Policy, 2018)
We introduce an environmental dimension into a real-business-cycle model augmented with a detailed government sector. We calibrate the model to Bulgarian data for the period following the introduction of the currency board arrangement (1999-2016). We investigate the quantitative importance of utility-enhancing environmental quality, and the mechanics of an "environmental" output tax levied on the polluting firm's output, as well as the effect of government spending on pollution abatement over the cycle. In particular, a positive shock to pollution emission in the model works like a positive technological shock, but its effect is quantitatively very small. Overall, the model performs relatively well when evaluated against data, but less so along the environmental dimension, so more research is needed to understand the aggregate effects of pollution.
Keywords: E32; C68; Q2; Q58; 330; Business cycles; pollution; environmental quality; environmental tax; abatement spending